The Influence of Learning Orientation and Human Capital on Absorptive Capacity in SMEs Rattan Cirebon - Anjuziani, Aros; Sa’adah, Aulia Fatihatus; Sahayani, Oki Putri (International Journal of Business, Law, and Education, 2024)
The purpose of this research is to examine how human capital and learning orientation affect absorptive capacity. This study used a quantitative research design. The small and medium-sized businesses (SMEs) that deal with rattan in Cirebon City are the study's demographic. Thirty-six companies provided 146 individuals for the samples. In this study, non-probability sampling is employed in conjunction with data withdrawal procedures and questionnaires with a Likert scale for measuring purposes. Multiple regression analysis with SPSS 26 is the data analysis method employed. The findings demonstrated that learning orientation and human capital characteristics had a favorable and significant impact on absorptive ability.